Moral Development Through The Boarding School Program - Nasution, Muhammad Ilyas; Magdalena, Magdalena; Harahap, Sumper Mulia (Fahmina: Jurnal Pendidikan Islam, 2023)
Boarding programs have long been an integral part of formal education in many countries. In addition to providing housing for students, the boarding program also has an important role in moral development. Moral formation through boarding programs involves developing strong moral, ethical, and personality values, which can shape the character of students to become responsible and ethical individuals. One of the main benefits of boarding programs in moral formation is to create an environment that supports positive personal growth. In a boarding environment, students learn to live together with people from different backgrounds, broadening their understanding of diversity, tolerance, and cooperation. This study looked at how the boarding program was carried out at the Darul Ikhlash Islamic Boarding School using qualitative research methods. From this research, the results of several excellent programs implemented at the Darul Ikhlash Islamic Boarding School were found, namely: congregational prayer, reading the Qur'an, book recitation, Tabligh, Muzakaroh, night study.